Legume phylogeny and classification in the 21st century: Progress, prospects and lessons for other species–rich clades. Issue 2 (27th December 2018) - ,; Bruneau, Anne; Doyle, Jeff J.; Herendeen, Patrick; Hughes, Colin; Kenicer, Greg; Lewis, Gwilym; Mackinder, Barbara; Pennington, R. Toby; Sanderson, Michael J.; Wojciechowski, Martin F.; Boatwright, Stephen; et al.
Abstract: The Leguminosae, the third–largest angiosperm family, has a global distribution and high ecological and economic impor tance. We examine how the legume systematic research community might join forces to produce a comprehensive phylogenetic estimate for the ca. 751 genera and ca. 19, 500 species of legumes and then translate it into a phylogeny–based classification. We review the current state of knowledge of legume phylogeny and highlight where problems lie, for example in taxon sampling and phylogenetic resolution. We review approaches from bioinformatics and next–generation sequencing, which can facilitate the production of better phylogenetic estimates. Finally, we examine how morphology can be incorporated into legume phylogeny to address issues in comparative biology and classification. Our goal is to stimulate the research needed to improve our knowledge of legume phylogeny and evolution; the approaches that we discuss may also be relevant to other species–rich angiosperm clades.